Distributed energy resources management using plug-in hybrid electric vehicles as a fuel-shifting demand response resource. (June 2015) - Morais, H.; Sousa, T.; Soares, J.; Faria, P.; Vale, Z.
Highlights: Definition fuel shifting demand response programs applied to the electric vehicles. Integration of the proposed fuel shifting in energy resource management algorithm. Analysis of fuel shifting contribution to support the consumption increasing. Analysis of fuel shifting contribution to support the electric vehicles growing. Sensitivity analysis considering different electric vehicles penetration levels. Abstract: In the smart grids context, distributed energy resources management plays an important role in the power systems' operation. Battery electric vehicles and plug-in hybrid electric vehicles should be important resources in the future distribution networks operation. Therefore, it is important to develop adequate methodologies to schedule the electric vehicles' charge and discharge processes, avoiding network congestions and providing ancillary services. This paper proposes the participation of plug-in hybrid electric vehicles in fuel shifting demand response programs. Two services are proposed, namely the fuel shifting and the fuel discharging. The fuel shifting program consists in replacing the electric energy by fossil fuels in plug-in hybrid electric vehicles daily trips, and the fuel discharge program consists in use of their internal combustion engine to generate electricity injecting into the network. These programs are included in an energy resources management algorithm which integrates the management of other resources. The paper presents a case study considering a 37-bus distribution network with 25 distributed generators, 1908 consumers, and 2430 plug-in vehicles. Two scenarios are tested, namely a scenario with high photovoltaic generation, and a scenario without photovoltaic generation. A sensitivity analyses is performed in order to evaluate when each energy resource is required.